Cigarette Smoking and Suicidal Behaviors in Colombian High-School Students. (July 2021) - Campo-Arias, Adalberto; Caballero-Domínguez, Carmen Cecilia; Suárez-Colorado, Yuli Paola
The study aimed to quantify the association between last-month cigarette smoking and lifetime suicide behaviors in high-school students at Santa Marta, Colombia. A cross-sectional study was designed in which high-school students participated. They were asked about last-month cigarette smoking and lifetime suicide behaviors (suicide ideation, plan, and attempt). Crude odds ratios (ORs) were calculated and adjusted for confounding variables. A total of 1, 462 students participated and they were between 13 and 17 ( M = 14.4, SD = 0.8) years, and 60.3% girls. The last-month prevalence of cigarette smoking was 11.6%, lifetime suicide ideation 10.2%, plan 18.5%, and attempted 15.4%. Cigarette smoking was associated with suicide ideation (OR = 1.67, 95% confidence interval [CI] = [1.17, 2.41]), suicide plan (OR = 1.97, 95% CI = [1.33, 2.93]), and suicide attempt (OR = 2.79, 95% CI = [1.87, 4.17]), after adjusting for gender, family function, and depressive symptoms. In conclusion, cigarette smoking is related to suicide behaviors in high-school students at Santa Marta, Colombia.